On the Empirics of Institutions and Quality of Growth: Evidence for Developing Countries - Simplice A. Asongu; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2015)
We explore a newly available dataset on quality of growth to investigate the effect of institutions on growth quality in 93 developing countries for the period 1990 to 2011. Quality of institutions is measured in term of political risk. The empirical evidence is based on: (i) Ordinary Least Squares (OLS) and Two Stage Least Squares (2SLS) and (ii) cross-sectional and panel data structures. In order to avail room for more policy implications, the dataset is further disaggregated into income levels, namely: Lower middle income (LMIC), low income (LI) and upper middle income (UMIC). Three main findings are established. First, institutions are positively related to the quality of growth. Second, institutions have significantly contributed to growth quality in increasing order during the following time intervals: 2005-2011, 1995-1999 and 2000-2004. Third, the positive nexus between institutions and growth quality is fundamentally driven by LMIC. Policy implications are discussed.
Keywords: O40; O55; I10; 330; Quality of growth; Institutions; Social indicators